THE UNSTEADY STATIC-STALL AERODYNAMIC CHARACTERISTICS OF AN S809 AIRFOIL AT LOW REYNOLDS NUMBERS - Fike, Matej; Bombek, Gorazd; Hriberšek, Matjaž; Hribernik, Aleš (Journal of Energy Technology, 2024)
An investigation was conducted to study the unsteady static-stall characteristics of an S809 airfoil whose aerodynamic characteristics are representative of a horizontal axis wind-turbine. It is very difficult to experimentally investigate this phenomenon, especially when attempting to study the development of flow-separation when the blades are rotating. The application of wind-tunnel tests or CFD simulation is obviously more appropriate. In order to investigate unsteady static-stall regarding the aerodynamic characteristics of an S809 airfoil, a comparative study was performed to obtain numerical and experimental results for the flow-separation position, airfoil pressure distribution, and velocity profiling that included velocity oscillations. The experimental results were acquired using PIV (Particle Image Velocimetry) and the study was performed at various angles of attack (AOA). No separation was observed at low AOA, but at 9.6° AOA the separation vortex comprised 50% of the airfoil’s chord length, whilst acomplete stalling of the airfoil occurred at 20° AOA. The observed separation zone was not steady but was found to oscillate around its mean-position at an interval of ± 10% of the chord’s length. Neither of the applied turbulence models k-ε nor SST used in 2D unsteady simulation predicted this oscillation, although the numerical results agreed fairly well with those experimentally obtained, especially the averaged velocity and vorticity fields around the suction side of the airfoil when using the SST model.
Keywords: S809 airfoil; low Reynolds number application; unsteady static-stal